Pendampingan Pembuatan Laporan Keuangan Sederhana Pada Home Industri Kripik Tempe Sumber Agung, Petoran, Jebres, Surakarta - Lamidi, Lamidi; Rahadhini, Marjam Desma (Indonesia Berdaya, 2022)
This community service activity takes the object of the Sumber Agung home industry in Petoran, Jebres, Surakarta. The main purpose of this service is to provide training and assistance to the owners of the Sumber Agung home industry in making simple financial reports, with the hope that business management will be able to separate business finances from personal finances. So that in managing the tempeh chips business, it can be seen in real terms in running their business, because they already have financial statements, although they are still simple. The problem faced, the tempe chips business that has been involved so far, is not able to show in real terms how much profit is earned per week or per month. This fact encourages the service team to do service with training methods and assistance in making simple financial reports. The training was carried out several times to the owner, then the team was still providing assistance, so that the owner was really able to make financial reports. The training is carried out in stages, starting with the steps of preparing transaction documents, recording financial transactions, separating transactions into ledgers, making work sheets, making capital changes, making trial balances and making profit and loss statements. As a result of this training and mentoring activity, the Sumber Agung home industry is able to make simple financial reports so that business management and business development can be seen in a real and correct way according to accounting rules. The output of this service activity is an article on service activities published in the National Accredited Journal